Use and predictors of health services among Australian children with mental health problems: A national prospective study - Sciberras, E; Hiscock, H; Mulraney, M; Sawyer, M; Coghill, D; Freed, G; Warren, H; Efron, D (My University, 2019)
Objective Retrospective, parent‐reported data suggest that 50% of Australian children with mental health disorders miss out on care. In a national sample, we aimed to determine the proportion receiving mental health services and associated characteristics, using prospective, objective data. Method Prospective analysis of linked Medicare Benefits Scheme (MBS)‐rebated mental health service use in children aged 8–9, 10–11, and 12–13 years, from the Longitudinal Study of Australian Children K cohort (N = 4,983). Analyses were conducted separately for children scoring above the cut points on the Strength and Difficulties Questionnaire (SDQ) emotional and externalising problems subscales. Characteristics were compared using logistic regressions. Results Nine to 27% of children scoring above SDQ cut points accessed MBS‐rebated mental health services, typically from general practitioners, psychologists and paediatricians. Greater symptom severity, parent perception that child needs help, being a young boy and older were associated with increased service use. Children from more disadvantaged families or families speaking a language other than English were less likely to receive services for internalising problems. Conclusion In the first prospective, objective analysis, most children do not receive mental health services.
Australian Journal of Psychology
Keywords: Health and wellbeing